Underwater vs. Conventional Endoscopic Submucosal Dissection: Retrospective Analysis from a German High-Volume Center - Ayoub, Mousa; Nagl, Sandra; Muzalyova, Anna; Römmele, Christoph; Cahyadi, Oscar; Quast, Daniel Robert; Messmann, Helmut; Ebigbo, Alanna (Zeitschrift für Gastroenterologie, 2025)
Endoscopic submucosal dissection (ESD) is an established technique for the resection of early neoplasia in the gastrointestinal tract (GIT). A further development of this technique is the resection under isotonic saline solution (underwater ESD or uESD), also referred to as Saline Immersion Therapeutic Endoscopy (SITE). Potential advantages include faster submucosal access and a reduced rate of intraprocedural complications, particularly submucosal bleeding. The primary objective of this retrospective, single-centre analysis was to provide the first data from Germany concerning the efficacy and safety of uESD and compare it to conventional ESD (cESD).This retrospective study analysed data from patients who underwent either uESD (n=36) or cESD (n=36). The control group (cESD) included lesions of similar location and size. Lesion selection was validated using propensity score matching. Treatment duration, complication rate, en-bloc resection rate, R0 resection rate, and recurrence rate were compared.A total of 72 ESD procedures were performed in 72 patients (36 undergoing uESD and 36 cESD). Per group, 11 procedures were performed in the esophagus, 3 in the stomach, 16 in the colon and 6 in the rectum. The median lesion size was 40 × 30 mm for uESD and 45 × 30 mm for cESD (p = 0.653). The median procedure time was similar (uESD: 77 minutes, cESD: 75 minutes, p = 0.088). The en-bloc resection rate was 100% in both groups, and the R0 resection rate was 94.4% (uESD) vs. 91.7% (cESD). The complication rate was low, with one post-ESD stricture in the uESD group (2.8%) and two post-ESD bleedings in the cESD group (5.6%) (p = 1.000). No postinterventional perforations occurred in either group.uESD is as effective and safe as cESD. Both techniques achieve high technical and clinical success rates with low complication rates. Future prospective studies should evaluate potential intraoperative advantages of uESD, such as the speed of submucosal entry and possible intraprocedural complications (e.g., bleeding, muscle injury).
Keywords: Endoscopic Submucosal Dissection; Underwater ESD; Conventional ESD